2008
DOI: 10.1016/j.chom.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

TLR-Independent Type I Interferon Induction in Response to an Extracellular Bacterial Pathogen via Intracellular Recognition of Its DNA

Abstract: SUMMARY Type I interferon (IFN) is an important host defense cytokine against intracellular pathogens, mainly viruses. In assessing IFN production in response to group B streptococcus (GBS), we find that IFN-β was produced by macrophages upon stimulation with both heat-killed and live GBS. Exposure of macrophages to heat-killed GBS activated a Toll-like receptor (TLR)-dependent pathway, whereas live GBS activated a TLR/NOD/RIG-like receptor (RLR)-independent pathway. This latter pathway required bacterial phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
137
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 59 publications
13
137
3
Order By: Relevance
“…Previously, we showed that GBS induces IFN-␤ production in a Toll-like receptor-independent fashion in macrophages by an unknown DNA sensor (12). We also showed that GBS induces IL-1␤ production in an NLRP3-dependent manner in dendritic cells (13).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we showed that GBS induces IFN-␤ production in a Toll-like receptor-independent fashion in macrophages by an unknown DNA sensor (12). We also showed that GBS induces IL-1␤ production in an NLRP3-dependent manner in dendritic cells (13).…”
mentioning
confidence: 99%
“…agalactiae strains NEM 316 (type III) were obtained from the blood of a neonate with sepsis as described (12). Strains NEM ⌬cylE and NEM ⌬cfb were NEM 316-derived mutants that lack CylE, a putative n-acetyltransferase in ornithine rhamnolipid biosynthesis, or CfB, which encodes the co-hemolysin (CAMP (Christie Atkins Munch-Petersen) factor), (12).…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the system responsible for double-stranded DNA (dsDNA)-induced innate immune responses, although extensively analyzed, is still unclear. Microbial dsDNA derived from bacteria and DNA viruses, as well as synthetic dsDNA, induce both type I IFN (IFN) production and other proinf lammatory cytokines, such as interleukin IL-1␤ and IL-6 (1)(2)(3)(4)(5)(6)(7)(8)(9). It is also known that undigested host genomic DNA accumulated in phagocytes can also induce aberrant activation of the immune response (10,11).…”
mentioning
confidence: 99%
“…Although production of type I IFNs was previously ascribed solely to antiviral immune responses (10), it now is well established that both intracellular (11)(12)(13)(14) and extracellular bacteria (11,(15)(16)(17) also induce transcription of these cytokines. Bacteria can elicit type I IFNs either by activating TLRs (11,12) or through TLR-independent recognition of bacterial pathogenassociated molecular patterns (PAMPs) within the host cell cytosol (11,18).…”
mentioning
confidence: 99%